2013
DOI: 10.1039/c3ib20231c
|View full text |Cite
|
Sign up to set email alerts
|

Hutchinson–Gilford progeria syndrome alters nuclear shape and reduces cell motility in three dimensional model substrates

Abstract: Cell migration through tight interstitial spaces in three dimensional (3D) environments impacts development, wound healing and cancer metastasis and is altered by the aging process. The stiffness of the extracellular matrix (ECM) increases with aging and affects the cells and cytoskeletal processes involved in cell migration. However, the nucleus, which is the largest and densest organelle, has not been widely studied during cell migration through the ECM. Additionally, the nucleus is stiffened during the agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 46 publications
8
57
0
Order By: Relevance
“…42,48 Nuclei deformation is most likely the result of a balance between the rigidity of the nucleus and the force that the cytoskeleton is able to exert on it. 23 All together, these results confirmed that cells could interact with the micropillar substrates and respond dynamically and spatiotemporally to the surrounding extracellular matrix.…”
Section: Effect Of the Micropillars On Cell Morphology Cytoskeletsupporting
confidence: 68%
See 1 more Smart Citation
“…42,48 Nuclei deformation is most likely the result of a balance between the rigidity of the nucleus and the force that the cytoskeleton is able to exert on it. 23 All together, these results confirmed that cells could interact with the micropillar substrates and respond dynamically and spatiotemporally to the surrounding extracellular matrix.…”
Section: Effect Of the Micropillars On Cell Morphology Cytoskeletsupporting
confidence: 68%
“…The specific geometric dimensions of micropillars in the array were chosen to expect to deform the cell morphology because they are close to cells sizes. 12,13,23 For clarity, the diameter of the micropillars and spacing between neighbor micropillars in the different arrays were denoted as d15, d18, and d18 lm and s15, s18, and s21 lm, respectively, in the next description. SEM image showed that the micropillars were well arranged on the substrate (Figures 1(e) and 1(f)).…”
Section: Resultsmentioning
confidence: 99%
“…However, traditionally the scratch assay has lacked a standardized set-up and quantification protocol, which has led to issues with reproducibility 7,10 . Many of the modifications and optimizations for improving the scratch assay have reduced these issues, including individual live-cell imaging, standardized stopper-based assays, and three dimensional micro-pillar assays 4,8,10 . However, these assays can be difficult to customize or adapt 10 and for some applications, these techniques can also be cost prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, such an assay must be sufficiently sensitive to detect relatively subtle changes in cellular migratory capacity after damage. Current methods for quantifying cell migration, including scratch assays, trans-well migration assays (Boyden chambers), micropillar arrays, and cell exclusion zone assays possess a range of limitations in reproducibility, customizability, quantification, and cost-effectiveness 1,4,5 . The optimized scratch assay described here demonstrates robust outcomes, quantifiable and image-based analysis capabilities, cost-effectiveness, and adaptability to other applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation